Scalable ultrarobust thermoconductive nonflammable bioinspired papers of graphene nanoplatelet crosslinked aramid nanofibers for thermal management and electromagnetic shielding. Issue 13 (11th March 2021) - Vu, Minh Canh; Park, Pyeong Jun; Bae, Sa-Rang; Kim, Soo Young; Kang, Young-Min; Choi, Won Kook; Islam, Md Akhtarul; Won, Jong Chan; Park, Manbok; Kim, Sung-Ryong
Abstract : Graphene nanoplatelets are chemically crosslinked to aramid nanofibers through a phosphorus trimer to fabricate ultratough, thermoconductive, flame retardant, and EMI shielding films. Abstract : With the rapid development of wearable electronic devices, multifunctional ultrarobust, thermoconductive, nonflammable, and electromagnetic interference (EMI) shielding films which are widely utilized to efficiently dissipate heat generated from electronic components are in high demand. The poor scalability and mechanical flexibility of multifunctional papers usually hinder their practical application. In this study, mass-scalable ultrarobust graphene nanoplatelet (GnP) cross-linked aramid nanofiber (ANF) papers with a nacre-bioinspired structure are fabricated via an evaporation-induced self-assembly approach. By chemical cross-linking between two-dimensional GnPs and one-dimensional ANFs in the nacre-bioinspired structure by a phosphorus agent, the excellent toughness and folding endurance of the GnP based ANF papers have been successfully achieved with simultaneous integration of high-level multifunctional properties. Specifically, the ultrarobust GnP based ANF paper with 50 wt% GnP loading exhibits exceptional ultimate tensile strength (437 MPa), Young's modulus (19.7 GPa) and toughness (23.9 MJ m −3 ) as well as superb folding endurance after 10 000 bending cycles. Moreover, the highly ordered alignment of GnP induced an unprecedented thermal/electrical conductivity, and the GnP (50 wt%) based ANF papers with an ultrathin thickness of 21 μm show a superb in-plane thermal conductivity (up to 68.2 W m −1 K −1 ) and outstanding absolute effectiveness EMI shielding (up to 11 060 dB cm 2 g −1 ) and are comparable with some commercial metals/alloys. These outstanding mechanical flexibility integrated superb thermal/EMI properties along with mass-scale production pave the way for practical applications of GnP based ANF papers in the development of advanced thermal management materials in autonomous cars, air vehicles and wearable devices.